Исследование ремесленного центра салтовской культуры - Колода, В.В. (Археологічні дослідження в Україні, 2010)
In 2009, the Mediaeval expedition of the Kharkiv National Pedagogical University started researching Mokhnach II settlement, the craftsman centre of Saltivska culture, dated by the period from the middle of the 8th c. to the middle of the 10th c., which belonged to the micro-region with the centre in Mokhnach hill-fort. Traces of quite developed smith’s and potter’s as well as mason’s production were discovered; there is indirect data on making ferrous metal of swamp ore here.